MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI PENERAPAN METODE CART SORT DI KELAS VII-1 SMP NEGERI 1 PATUMBAK - Umu Hani (JS (JURNAL SEKOLAH), 2020)
Abstract: Improving Student Learning Outcomes in Learning Islamic Religious Education Through the Application of Cart Sort Method in Class VII-1 Middle School 1 Patumbak. The percentage of students completeness in the first cycle was 61.1% or as many as 22 students out of 36 students who had completed grades. cycle II also increased the average value from 73 in the test after the first cycle to 84 in the test after the second cycle. The cycle I action of students who reached the KKM increased by 63%, and in the evaluation test after the cycle II action also increased to 89%. The achievement of KKM shows that students have succeeded in achieving the specified minimum completeness criteria. The results obtained are considered sufficient, because indicators of success in this study have been achieved. Keywords: Learning Outcomes, Card Sort Method Abstrak: Meningkatkan Hasil Belajar Siswa Dalam  Pembelajaran Pendidikan Agama Islam Melalui Penerapan Metode Cart Sort  Di Kelas VII-1 SMP Negeri 1 Patumbak. PersentaseketuntasansiswapadasiklusI sebesar61.1%atausebanyak22 siswadari36 siswayang mendapatnilaituntas. siklusII jugaterjadipeningkatannilairata-ratadari73padatessetelah tindakansiklusI menjadi84padatessetelahtindakansiklusII.TindakansiklusIsiswayangmencapaiKKM mengalamipeningkatanyaitusebesar 63%,danpada tesevaluasisetelah tindakansiklusII meningkatpulamenjadi89%.PencapaianKKM menunjukkanbahwa siswatelahberhasilmencapaikriteria ketuntasan minimalyang telahditentukan.Hasilyang diperolehdirasasudahcukup, karenaindikator keberhasilan dalam penelitian initelah tercapai. Kata Kunci :Hasil Belajar, Metode Card Short